Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/ieam.1588
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ecological risks to the fish community from residual coal fly ash in Watts Bar Reservoir, Tennessee

Abstract: EDITOR'S NOTE:The Baseline Ecological Risk Assessment (BERA) of residual coal-fly ash in Watts Bar Reservoir was conducted following a 2008 spill from the Tennessee Valley Authority Kingston Fossil Plant (Roane County, TN). Results of the BERA were used to focus the long-term management strategy for the impacted river system. This article is among 7 peer-reviewed articles in the special series, "Ecological Risk Assessment for Residual Coal Fly Ash at Watts Bar Reservoir, Tennessee." The series includes article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Fish community surveys were given the greatest weight in the estimation of risk to fish. Similar to the benthic community surveys, they indicated no ecologically important impacts to individuals due to residual ash that might subsequently be manifested at population or community levels (Rigg et al , this issue). The results of fish toxicity tests, reproductive competence evaluations, and fish health studies also suggested no notable adverse effects of the ash at the organism or suborganism level (Rigg et al , this issue).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Fish community surveys were given the greatest weight in the estimation of risk to fish. Similar to the benthic community surveys, they indicated no ecologically important impacts to individuals due to residual ash that might subsequently be manifested at population or community levels (Rigg et al , this issue). The results of fish toxicity tests, reproductive competence evaluations, and fish health studies also suggested no notable adverse effects of the ash at the organism or suborganism level (Rigg et al , this issue).…”
Section: Introductionmentioning
confidence: 79%
“…The 17 receptor groups evaluated included fish, benthic invertebrates, aquatic plants (periphyton and macrophytes), and wildlife that feed in and around the river system (see conceptual site model in Figure 2 in Walls, Jones et al 2015, this issue). BERA details are available in the project report (ARCADIS ), and details for several receptors are presented in 5 other articles in this series (Buys et al , Meyer et al , Rigg et al , Stojak et al , Walls, Meyer et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These various types of samples were used to estimate bioavailability and bioaccumulation of COPECs from diet and other exposure pathways, as well as to model bioavailability to the respective predators. Subsequent articles focus on the evaluations for fish (Rigg et al , this issue), benthic invertebrates (Buys et al , this issue, and Stojak et al , this issue), aquatic‐ and riparian‐feeding wildlife (Meyer et al , this issue), and aerial‐feeding insectivores (i.e., tree swallows; Walls et al , this issue).…”
Section: Study Approachmentioning
confidence: 99%
“…They were evaluated at the suborganism level, assessing molecular, biochemical and physiological endpoints. Fish health metrics in this study included reproductive condition (ovary stage, oocyte condition, estimation of fecundity), gonadosomatic index (GSI) (relative size of gonad to body size), bioenergetic and hematological responses, histopathological indicators, indicators of carbohydrate‐protein metabolism, organ dysfunction responses, measures of electrolyte homeostasis, and indices of feeding and nutrition (parameters associated with digestive physiology) (Rigg et al , this issue; Bevelhimer et al ). Avian health metrics included tree swallow, heron, and osprey egg weight, volume, length, and width.…”
Section: Measurement Endpointsmentioning
confidence: 99%